Effects of Watching Violence Movies On The Attudes Concerning Aggression Among Middle Schoolboys (13-17 years old) at International Schools In Kuala Lumpur, Malaysia. - Hassan, Md Salleh; Osman, Mohd Nizam; Azarian, Zoheir Sabaghpour (EuroJournals Publishing, Inc., 2009)

(untitled)
Violence is one of the global concerns today in all segments of the world.Antisocial behaviour in human beings is accepted to be associated to a number of physiological, psychological, domestic, and cultural aspects. The learning environments which a child is exposed are also assumed to contribute to the increase of aggressive behaviour and attitudes. Media violence as one of specific learning condition is believed to be a potential contributor to the growth of antisocial behaviour in children and youth. Many studies have been conducted in the area of media violence and its effects on the young viewers. A major focus has been the relationship between media violence and aggressive behaviour but, interestingly, research regarding the relationship between media violence and attitudes about aggression is limited. The purpose of this study, therefore, was to contribute to the state of the research by predicting and comparing attitudes about aggression among adolescent boys on the basis of their exposure to violence in movies. This study used a survey research design. Two hundred and sixteen adolescent boys aged 13-17 were selected from seven international schools located in Kuala Lumpur. The data were collected using four instruments: the Demographic Questionnaire, the Media Viewing Habit Questionnaire, the Affection toward movie violence scale, and the Attitudes concerning Aggression Scale. The results indicated that adolescent boys spend a significant amount of time watching movies on TV and DVD/CD as well. In addition, they are Effects of Watching Violence Movies on the Attitudes Concerning Aggression among Middle Schoolboys (13-17 years old) at International Schools in Kuala Lumpur, Malaysia 142 exposed to substantial amounts of media violence. At the same time, parental involvement with their adolescents’ movie viewing is relatively limited. Further results showed that there is significant difference between heavy and light viewers of movie violence in any dimension of their attitudes about aggression.Adolescents with “violent” movies preferred, however, were significantly more supportive of the attitude that aggression is acceptable and warranted, as compared to those who prefer movies with little or no violence. Additional results demonstrated that the "aggressionacceptable" attitude was significantly related to a set of variables. The strongest predictors of this attitude in adolescent boys were affection toward movies, movie viewing habits, and the adolescents' movies preferred. The results obtained in this research are discussed in terms of implications for both violence-prevention programs and media-awareness programs. Suggestions for future research are also presented.